Collaborative Primary Mental Health Education for Correctional Nurses. (January 2019) - Trimmer, Wendy; Fuller, Catherine; Kake, Christina; Asbury, Elizabeth
Whitireia New Zealand and the Department of Corrections have worked collaboratively since 2008 in developing and delivering primary mental health (PMH) training for registered correctional nurses, specifically focused on assessment and brief interventions applicable to a primary health setting. The PMH training program was undertaken and evaluated by Department of Correction nurses between 2009 and 2016. Significant improvements in PMH learning outcomes were noted among 396 participants, while98% applied knowledge gained from the PMH workshops to their practice. This highly successful educational collaboration has enhanced nurses' knowledge and skills in recognizing and managing PMH issues within the prison environment.